Effects of supervised exercise on cancer-related fatigue in breast cancer survivors: a systematic review and meta-analysis (2015)
Background Cancer-related fatigue (CRF) is the most common and distressing symptom in breast cancer survivors. Approximately 40% to 80% of cancer patients undergoing active treatment suffer from CRF. Exercise improves overall quality of life and CRF; however, the specific effects of the training modalities are not well understood. Methods This study aimed to determine the pooled effects of supervised exercise interventions on CRF in breast cancer survivors. We searched PubMed/MEDLINE, EMBASE, Scopus, CENTRAL and CINAHL databases between December 2013 and January 2014 without language restrictions. Risk of bias and methodological quality were evaluated using the PEDro score. Pooled effects were calculated with a random-effects model according to the DerSimonian and Laird method. Heterogeneity was evaluated with the I2 test. Results Nine high-quality studies (n?=?1156) were finally included. Supervised aerobic exercise was statistically more effective than conventional care in improving CRF among breast cancer survivors (SMD?=??0.51, 95%CI ?0.81 to ?0.21), with high statistical heterogeneity (P?=?0.001; I2?=?75%). Similar effects were found for resistance training on CRF (SMD?=??0.41, 95%CI ?0.76 to ?0.05; P?=?0.02; I2?=?64%). Meta-regression analysis revealed that exercise volume parameters are closely related with the effect estimates on CRF. Egger’s test suggested moderate evidence of publication bias (P?=?0.04). Conclusions Supervised exercise reduces CRF and must be implemented in breast cancer rehabilitation settings. High-volume exercises are safe and effective in improving CRF and overall quality of life in women with breast cancer. Further research is encouraged.